Anti-Apoptotic Signature in Thymic Squamous Cell Carcinomas – Functional Relevance of Anti-Apoptotic BIRC3 Expression in the Thymic Carcinoma Cell Line 1889c - Huang, Bei; Belharazem, Djeda; Li, Li; Kneitz, Susanne; Schnabel, Philipp; Rieker, Ralf; Körner, Daniel; Nix, Winnfried; Schalke, Berthold; Müller-Hermelink, Hans Konrad; Ott, German; Rosenwald, Andreas; et al. (Frontiers in Oncology, 2013)
The molecular pathogenesis of thymomas and thymic carcinomas (TCs) is poorly understood and results of adjuvant therapy are unsatisfactory in case of metastatic disease and tumor recurrence. For these clinical settings, novel therapeutic strategies are urgently needed. Recently, limited sequencing efforts revealed that a broad spectrum of genes that play key roles in various common cancers are rarely affected in thymomas and thymic carcinomas, suggesting that other oncogenic principles might be important. This made us re-analyze historic expression data obtained in a spectrum of thymomas and thymic squamous cell carcinomas (TSCC) with a custom made cDNA microarray. By cluster analysis, different anti-apoptotic signatures were detected in type B3 thymoma and TSCC, including overexpression of BIRC3 in TSCCs. This was confirmed by qRT-PCR in the original and an independent validation set of tumors. In contrast to several other cancer cell lines, the BIRC3-positive TSCC cell line, 1889c showed spontaneous apoptosis after BIRC3 knock-down. Targeting apoptosis genes is worth testing as therapeutic principle in TSCC.